Radiocarbon Analyses Quantify Peat Carbon Losses With Increasing Temperature in a Whole Ecosystem Warming Experiment. Issue 11 (10th November 2021) - Wilson, Rachel M.; Griffiths, Natalie A.; Visser, Ate; McFarlane, Karis J.; Sebestyen, Stephen D.; Oleheiser, Keith C.; Bosman, Samantha; Hopple, Anya M.; Tfaily, Malak M.; Kolka, Randall K.; Hanson, Paul J.; Kostka, Joel E.; et al.
Abstract: Climate warming is expected to accelerate peatland degradation and release rates of carbon dioxide (CO2 ) and methane (CH4 ). Spruce and Peatlands Responses Under Changing Environments is an ecosystem‐scale climate manipulation experiment, designed to examine peatland ecosystem response to climate forcings. We examined whether heating up to +9 °C to 3 m‐deep in a peat bog over a 7‐year period led to higher C turnover and CO2 and CH4 emissions, by measuring 14 C of solid peat, dissolved organic carbon (DOC), CH4, and dissolved CO2 (DIC). DOC, a major substrate for heterotrophic respiration, increased significantly with warming. There was no 7‐year trend in the DI 14  C of the ambient plots which remained similar to their DO 14  C. At +6.75 °C and +9 °C, the 14 C of DIC, a product of microbial respiration, initially resembled ambient plots but became more depleted over 7 years of warming. We attributed the shifts in DI 14  C to the increasing importance of solid phase peat as a substrate for microbial respiration and quantified this shift via the radiocarbon mass balance. The mass‐balance model revealed increases in peat‐supported respiration of the catotelm depths in heated plots over time and relative to ambient enclosures, from a baseline of 20%–25% in ambient enclosures, to 35%–40% in the heated plots. We find that warming stimulates microorganisms to respire ancient peat C, deposited under prior climate (cooler) conditions. This apparent destabilization of the large peat C reservoir has implications for peatland‐climate feedbacks especially if the balance of the peatland is tipped from net C sink to C source. Plain Language Summary: Since the end of the last glacial period, about 20 thousand years ago, peatlands have taken up carbon and now store an amount nearly equivalent to the quantity in the atmosphere. Microorganisms consume and respire that peat C releasing it back to the atmosphere as CO2 and CH4 . Until now, many studies have shown that microorganisms prefer to consume the most recently fixed carbon and that the deeply buried ancient peat carbon reservoir is relatively stable. However, climate warming is expected to upset that balance. The Spruce and Peatlands Responses Under Changing Environments is large‐scale experimental warming of a Minnesota peatland designed to study these effects. We conducted radiocarbon analysis of the peat and the microbially produced CO2 and dissolved organic carbon in ambient and heated areas of the peatland and show that at warmer temperatures more of the ancient peat carbon is being mobilized and respired to CO2 . This is troubling as it signifies a positive feedback loop wherein warming stimulates peat to produce more CO2 which further exacerbates climate change. Key Points: Radiocarbon mass balance demonstrates the loss of peat carbon in a peatland ecosystem warming experiment Peat carbon losses increased with warming treatment Tritium‐based analyses calculate approximately 30 cm y −1 downward advection of porewater through the top 1 m of peat